Radioimmunoassay for 6-D-tryptophan analog of luteinizing hormone-releasing hormone: measurement of serum levels after administration of long-acting microcapsule formulations. - Mason-Garcia, M (1985)
A sensitive and specific radioimmunoassay for [6-D-tryptophan]luteinizing hormone-releasing hormone [( D-Trp6]LH-RH) was developed and used for following the rate of liberation of [D-Trp6]LH-RH from a long-acting delivery system based on a microcapsule formulation. Rabbit antibodies were generated against [D-Trp6]LH-RH conjugated to bovine serum albumin with glutaraldehyde. Crossreactivity with LH-RH was less than 1%; there was no significant crossreactivity with other peptides. The minimal detectable dose of [D-Trp6]LH-RH was 2 pg per tube. Intra- and interassay coefficients of variation were 8% and 10%, respectively. The radioimmunoassay was suitable for direct determination of [D-Trp6]LH-RH in serum, permitting the study of blood levels of the analog after single injections into normal men and after once-a-month administration of microcapsules to rats. In men, 90 min after subcutaneous injection of 250 micrograms of the peptide, serum [D-Trp6]LH-RH rose to 6-12 ng/ml. Luteinizing hormone was increased 90 min and 24 hr after the administration of the analog. Several batches of microcapsules were tested in rats and the rate of release of [D-Trp6]LH-RH was followed. The improved batch of microcapsules of [D-Trp6]LH-RH increased serum concentrations of the analog for 30 days or longer after intramuscular injection. This was accompanied by suppression of testosterone levels for more than 30 days. This radioimmunoassay should be of value for monitoring [D-Trp6]LH-RH during long-term therapy.